Extraction of Non-Ferrous Metals and Iron with Systems based on Bis(2, 4, 4-Trimethylpentyl)Dithiophosphinic Acid (CYANEX 301), A Review. Issue 1 (2nd January 2018) - Fleitlikh, I. Yu.; Grigorieva, N. A.; Logutenko, O. A.
ABSTRACT: Extraction is widely used in the hydrometallurgy of nonferrous metals. In addition to such well-known extractants as oxygen-containing organophosphorus or monocarboxylic acids, thio-substituted organophosphorus acids in particular, the commercially available extractant CYANEX 301, the active component of which is bis(2, 4, 4-trimethylpentyl)dithiophosphinic acid (HR), is of interest. This extractant is a sulfur-containing analogue of CYANEX 272 (bis(2, 4, 4-trimethylpentyl) phosphinic acid). In this review, the state of CYANEX 301 in various solvents in the absence and presence of electron-donor additives, the chemistry of the extraction processes of non-ferrous metals in the HR systems, the compositions of the extracted compounds, stability of the extractant in aggressive media, technological developments, and prospects for using CYANEX 301 in hydrometallurgy of non-ferrous metals are discussed.